PENGEMBANGAN AUTOMATIC DEPENDENT SURVEILLANCE â BROADCAST UNTUK PENINGKATAN KESELAMATAN PENERBANGAN - Sitorus, Budi; Sitorus, Tulus Irfan Harsono (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
The purpose of this study is to conduct a review of the existing navigation system at the airport and integrate to the flight navigation system that has been developed by the Ministry of Research and Technology to be applied to Airports in Indonesia. The research method used is qualitative research method through literature study, literature, benchmarking. Automatic Dependent Surveillance Broadcast (ADS-B) is a system designed to replace radar functions in air space management for civilian transport, can serve as a substitute or for traditional radar-based aircraft surveillance supplements. The use of ADS-B was recommended by the International Civil Aviation Organization (ICAO) in May 2006. Using ADS-B, detection would be better and more accurate than when using a radar system where existing radar systems can not detect unobstructed aircraft . The use of the ADS-B system in Indonesia began in 2006, in partnership with SITA and Thales. In this regard, Indonesia has 30 (thirty) earth stations ready for operation. In general, both flight monitoring systems are very helpful for APP operators (Approach and departure control) in terms of providing a picture of flight traffic conditions around the airport.